Diversity and Feeding Guild of Birds Along Gradient of Revegetated Area in Karst Ecosystem: a Case Study from Rembang, Central Java (Biosaintifika: Journal of Biology & Biology Education, 2022)
In the mining industry, provision of new habitat through land rehabilitation and affforestation is an important step to anticipate the loss of biodiversity, including bird communities. The positive impacts of land rehabilitation and affforestation thus can be identified from results of periodic monitoring. The turnover of bird communities associated with afforestation is related to changes in structural habitat features that provide food and shelter. In this study, we have monitored bird community assemblages and feeding guild structure in revegetated area of karst in Rembang, Central Java. Three locations (EDP, GBC and GBL) were selected and characterized by different land use, vegetational age and floral composition. Surveys were conducted using point count method in early April for three consecutive years (2020-2022). In total, we have identified 32 bird species from 29 genera, 22 families and 9 orders. Most of birds observed considered as generalist, cosmopolitan and well-adapted to various habitat. Total species richness (19.33±3.22 to 20.67±4.12) and value of diversity index (H’ = 2.41±0.14 to 2.56±0.29) were only slightly differed among locations. Species richness and total abundance in each sites tend to increase along periods of observation, suggesting that bird community change in response to further structural habitat changes that occur as vegetations age. Furthermore, higher abundance occurred in larger area or in sites with more native plant species. The feeding guild costisting 7 groups and dominated by insectivore, both based on number of species (46.88%) and individuals (49.07%). Results of the study are expected to help identify more appropriate management of conservation and habitat restoration in the area.